Design and Synthesis of Novel 1-substituted-3-(3-(3-nitrophenyl)-4-oxo-3,4-dihydrobenzopyrimidin-2-yl amino) Isothioureas for their Anti-HIV, Antibacterial Activities, Graph Theoretical Analysis, Insilico Modeling, Prediction of Toxicity and Metabolic Studies - Narendhar, Bandi; Alagarsamy, Veerachamy; Krishnan, Chitra (Drug Research, 2020)
In the present study, we have placed the substituted thiosemicarbazide moiety at the C-2 position and 3-nitrophenyl group at N-3 position of benzopyrimidines and studied their antitubercular, anti-HIV and antibacterial activities against selected gram positive and negative bacteria. The target compounds 1-substituted-3-(3-(3-nitrophenyl)-4-oxo-3,4-dihydrobenzopyrimidin-2-ylamino) isothioureas (PTS1 – PTS15 ) were obtained by the reaction of 2-hydrazino-3-(3-nitrophenyl) benzopyrimidin-4(3 H)-one (5) with different alkyl/aryl isothiocyanates followed by methylation with dimethyl sulphate. All synthesized compounds were screened for their antitubercular, anti-HIV and antibacterial activity against selective gram positive and gram negative bacteria by agar dilution method. Among the series, compound 2-methyl-3-(3-(3-nitrophenyl)-4-oxo-3,4-dihydrobenzopyrimidin-2-ylamino)-1-(3-chlorophenyl)isothiourea (PTS14) shown most potent activity against Klebsiella pneumoniae, Proteus vulgaris and Staphylococcus aureus; PTS14 exhibited the antitubercular activity at the minimum microgram of 1.56 µg/mL and anti-HIV activity at 0.96 µg/mL against HIV1 and HIV2 and offers potential for further optimization and development to new antitubercular and anti-HIV agents. The results obtained from this study confirm that the synthesized and biologically evaluated benzopyrimidines showed promising antimicrobial, antitubercular and anti-HIV activities and are new scaffolds for antimicrobial activity.
Keywords: condensed pyrimidine; graph theoretical analysis; substituted thiosemicarbazide; antibacterial activity; antitubercular activity; anti-HIV activity